Formation and stability of long basal-prismatic facets in Mg. (15th February 2020) - Dang, Khanh; Wang, Shujuan; Gong, Mingyu; McCabe, Rodney J.; Wang, Jian; Capolungo, Laurent
Abstract: Long BP facets bounding 10 1 ¯ 2 〈 1 ¯ 011 〉 twins in Mg ( ≥ 4 nm) have been observed experimentally. However, the formation of these long BP facets has not been studied and their contribution/role to the twin growth remains unclear. We observe a long straight BP facet (27 nm) using high-resolution transmission electron microscopy (HRTEM) and investigate its formation, stability, and mobility by atomistic simulations. Experimentally, a serrated twin interface containing short CTBs and short BP facets near a ( 10 1 ¯ 2 ) twin tip is observed to transform under the effects of the electron beam into a long straight semi-coherent BP facet that contains disclination dipoles. Molecular dynamics (MD) simulations of the relaxation of a 3D twin domain reveals another process whereby a long partially-relaxed BP interface forms and contains an I2 stacking fault. A comparison between the energy of these configurations as obtained by atomistic simulations suggests that these transformations occur in two steps: (1) serrated interfaces composed of coherent BP segments with lengths less than 2 nm combine and form a long and straight coherent BP facets and (2) these long coherent BP facets quickly transform into relaxed ones with misfit defects. Importantly, it is found that long BP facets are relatively immobile, and upon reloading, decay into more mobile serrated interfaces prior to migrating. The work presented suggests that the atomistic configurations of BP facets during twin growth processes differ significantly from relaxed BP interfaces that would be observed by TEM. Graphical abstract: Image, graphical abstract